Will consumers purchase Stevia as a sugar substitute?: an exploratory study on consumer acceptance - Kamarulzaman, Nitty Hirawaty; Jamal, Kasazlinda; Vijayan, Gowri; Ab. Jalil, Siti Munirah (Routledge, 2014)
Stevia rebaudiana Bertoni, commonly known as Stevia, is an ancient sweet herb native to Paraguay. The plant, especially the leaves, has a sweetening effect 300 times sweeter than saccharose. Malaysia has taken a particular interest in promotion of Stevia derivatives as a precautionary measure to combat chronic diseases. This study aims to investigate factors that influence the acceptance of Stevia-based products by consumers. Face-to-face interviews were conducted using a structured questionnaire with 900 consumers from Klang Valley areas. The results revealed that most of the respondents were willing to use Stevia-based products as a substitute for sugar. There was also a significant relationship between level of education and consumer’s willingness to change for Stevia-based products. Health benefits, promotion, availability, and price were found to be the most influential factors toward acceptance of Stevia-based products by consumers. An effective promotion is necessary to increase consumer’s awareness toward a more healthy diet.